Deixis and Digital Persuasion: Sociopreneurship Messages of @aldwinnv on Instagram and TikTok - Ari Astutik; Dewanto; Lambang Erwanto (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
This study looks at how deixis shapes persuasive sociopreneurship posts on Instagram and TikTok, using six posts by Indonesian sociopreneur @aldwinnv as examples. Deixis, which links language to the speaker, audience, and context, plays a key role in how messages persuade online. By analyzing the posts with a qualitative descriptive approach, the study highlights five types of deixis: personal, temporal, spatial, social, and discourse. Words like I and we (personal deixis) build trust and closeness with followers. Temporal cues such as now and today create a sense of urgency, pushing readers to take action. Spatial references, like here or this place, make the stories feel grounded and real. Social deixis—terms like friends or guys—varies in tone: more formal on Instagram, more casual and friendly on TikTok. Discourse markers such as as I mentioned earlier help the narrative flow and stay coherent. In short, deixis isn’t just a technical language feature-it’s a persuasive tool. It strengthens credibility, engages emotions, and fosters a sense of community around sociopreneurship content. This research adds to digital pragmatics by showing how small language choices can have a big impact and offers practical insights for teaching media literacy and entrepreneurship.